2008
DOI: 10.1631/jzus.b0710636
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of root morphology to potassium deficient stress among rice genotypes varying in potassium efficiency

Abstract: Disparity in the root morphology of six rice (Oryza sativa L.) genotypes varying in potassium (K) efficiency was studied with three K levels: 5 mg/L (low), 10 mg/L (moderate) and 40 mg/L (adequate) in hydroponic culture. Morphological parameters included root length, surface area, volume and count of lateral roots, as well as fine (diameter<0.2 mm) and thick (diameter>0.2 mm) roots. The results indicate that the root growth of all genotypes was reduced under low K, but moderate K deficiency increased the root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 19 publications
(24 reference statements)
6
44
0
1
Order By: Relevance
“…Since K + is the main osmotic cation in plant root cells, it is reasonable to surmise that K + deficiency would arrest root growth (Armengaud et al 2004;Dolan and Davies 2004;Shin and Schachtman 2004;Jung et al 2009;Zhang et al 2009;Jia et al 2008;Ma et al 2012;Gruber et al 2013;Kellermeier et al 2013). However, the mechanism by which K + deficiency inhibits root growth remains unclear, even in the model plant Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since K + is the main osmotic cation in plant root cells, it is reasonable to surmise that K + deficiency would arrest root growth (Armengaud et al 2004;Dolan and Davies 2004;Shin and Schachtman 2004;Jung et al 2009;Zhang et al 2009;Jia et al 2008;Ma et al 2012;Gruber et al 2013;Kellermeier et al 2013). However, the mechanism by which K + deficiency inhibits root growth remains unclear, even in the model plant Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis [Armengaud et al 2004;Shin and Schachtman 2004;Jung et al 2009], cotton [Zhang et al 2009] and rice [Jia et al 2008;Ma et al 2012]). In a classic study, Drew (1975) demonstrated increased lateral root (LR) growth in barley seedlings when K + was supplied only to selected portions of the root system.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that root architecture and plasticity reveal a response of plants to scarce nutrients, and natural variation exists for these traits in different species, related to potassium (Kellermeier et al 2013;Jia et al 2008), nitrogen (De Pessemier et al 2013, and phosphorus availability (Wang et al 2010). Natural variation for NUpE has been shown directly by measuring a specific mineral content in different genotypes, as Burns et al demonstrated for nitrate in different varieties of lettuce.…”
Section: Investigation Of Natural Variation In Plants Reveals Differementioning
confidence: 99%
“…Cd is a non-essential element that negatively affects plant growth and development processes, such as respiration and photosynthesis (Greger and Ögren, 1991;Baryla et al, 2001;Vega et al, 2006), water and mineral uptakes (Singh and Tewari, 2003), cell division (Fojtová et al, 2002), and cellular redox homoeostasis (Romero-Puertas et al, 2004). From the viewpoint of water and nutrient uptakes, roots are of particular physiological importance (Bosac et al, 1995;Jia et al, 2008). Fine roots are usually more sensitive to exposure to either excessive metal concentrations (Arduini et al, 1995) or elevated levels of CO 2 (Day et al, 1996;Janssens et al, 1998;Phillips et al, 2006) when compared to coarse roots.…”
Section: Introductionmentioning
confidence: 99%